If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5x + -4) = 21 Reorder the terms: -3(-4 + 5x) = 21 (-4 * -3 + 5x * -3) = 21 (12 + -15x) = 21 Solving 12 + -15x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -15x = 21 + -12 Combine like terms: 12 + -12 = 0 0 + -15x = 21 + -12 -15x = 21 + -12 Combine like terms: 21 + -12 = 9 -15x = 9 Divide each side by '-15'. x = -0.6 Simplifying x = -0.6
| (-7p/2)=(-7/8) | | 13x^2+21=-5x^2+22 | | (-7p/2)(-7/8) | | 32x=1 | | (2-7x)+(2x+1)= | | 2-4x=4x+10 | | 5-2n=5 | | 4x+9=34x | | 4x=2x+2+3x-3 | | 0=6(x+2)(x-1) | | x^4-10x^2+34=0 | | 9x+6=27 | | X/2=57 | | 5/3=y/9 | | R(4)= | | 7x+280=8x+278 | | F(3)+3= | | 5(3x+4)=0 | | 34=3x+10 | | 5w+7-2(-7w-4)=3(w-1) | | 5(3x-4)=0 | | 4a^2+10a-22=0 | | 14c-6c= | | -11+6+7n-9n=n+1 | | 4x-2(5x-8)=-56 | | (6x)=6(xy) | | 2m^2-7m-7m-13=-10 | | 5w-5+2(3w+7)=-5(w+1) | | 15u-8u=49 | | 6=4x/(12-x) | | X-2(-.3)=2 | | 13=5x+11 |